The Effect of Learning Agility, Self-Concept, and Family Support on Student Academic Burnout in Accounting Students - Sultan Habib; Lisa Martiah Nila Puspita (Proceeding International Conference on Accounting and Finance, 2025)
The phenomenon of Student Academic Burnout has recently become a concern in many countries in the world, especially its impact on student academic performance. The factors that cause students to experience Student Academic Burnout are currently growing. One of the causes is the change in the pattern of activities in the world of education. It includes optimizing the role of technology and an increasingly competitive environment that requires students to adapt faster. The purpose of this research is to test whether students who have a high level of Learning Agility, have good Self-Concept, and get a lot of Family Support from the family environment experience Student Academic Burnout at a low level. The population was all active accounting students in Indonesia, totaling 417,882 people. The sample in this study was calculated using the Slovin formula (1960) and obtained sample results of 400 people. The measurement tools are the Maslach Burnout Inventory-Student Survey (MBI-SS), Learning Agility Scale, Personal Self-Concept (PSC), and Family Support Scale (FSS). By using multiple regression, the results indicate all variables simultaneously have an effect of 73.2% in suppressing and reducing Student Academic Burnout. This study also found that Learning Agility, Self-Concept, and Family Support have a significant negative effect on Student Academic Burnout. This means that the higher the level of all independent variables, the lower the level of Student Academic Burnout that can be experienced by students. This article also explains the implications and limitations of the research conducted.